Synthesis of Chitosan−Al2O3 Composite using the Sol-Gel Method and Its Application in Photodegradation of Methylene Blue - Desnelli Desnelli; Ipro Hati Padilah; Maria Ulfa; Eliza Eliza; Ady Mara; Fatma Fatma (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
The research on synthesis of composites Kitosan-Al2O3 by the sol-gel method for photodegradation of methylene blue has been carried out. Chitosan-Al2O3 varied by mass ratios (1:1), (1:2) and (1:3). The product were characterized using XRD and UV-DRS. Chitosan-Al2O3 ratio (1:1) were characterized by SEM-EDS. The best material will be used to degrade the mehtylene blue by various condition, i.e., effect of pH, contact time and initial concentration of methylene blue. The Chitosan-Al2O3 (1:1) composite was chosen as a material for degrading methylene blue. The result of characterization using XRD showed crystal size the Chitosan- Al2O3 (1:1) composites result were 3,17 nm. UV-DRS characterization, The band gap energy is 1,35 eV. The morphological condition by SEM of Chitosan-Al2O3 ratio (1:1) showed a spherical shape with a small size, and a porous surface the constituent elements C (4.93%), O (33.31%), Na (13.92%), Al (45.59%) dan Zn (2.24%). The degradation process showed the effective condition were pH 10 and contact time of 200 minutes. The optimum concentration of methylene blue at 20 ppm with percent effectivity of concentration reduction methylene blue i.e. 79.35% and the result of TOC analysis i.e. 22,36%. The Chitosan-Al2O3 can be used to degraded the Methylene blue.